Penerapan Pembelajaran Bilingual pada Anak Usia Dini di Desa Kabuna Haliwen Atambua, Nusa Tenggara Timur - Christina Anugrahini; Sefrina Maria Seukasa; Deonizia Luchita Paulus (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
In general, people in the world today have bilingualism to communicate. Without language, a person will not be able to communicate with others. So this language skill must be developed since children are at an early age. Language development begins in infancy and relies on its role in experience, mastery and language growth. Children learn language since infancy where before learning to speak they communicate through crying, smiling and body movements. Learning language is very crucial at the age of before six years. Therefore, early childhood education is a very important vehicle in developing children's language so that this condition can facilitate the development of language skills in early childhood. This study aims to identify the application of bilingual learning in early childhood in the village of Kabuna Haliwen Atambua, East Nusa Tenggara. The design of this study is quantitative with a pre and post control approach. 12 early childhood children in Kabuna Haliwen Atambua Village, East Nusa Tenggara. The largest number of early childhood children is 6 years old, 5 people, 3 people, and 4 years old. gender is male, 7 people and female, 5 people. The Implementation of Bilingual Learning in Early Childhood has increased by 37% from an average of 60% to 97%. The implementation of bilingual learning in early childhood is very important to be implemented in everyday life. Implement the Implementation of Bilingual Learning through simulation activities. Become evidence in the development of English language science, especially in improving the Implementation of Bilingual Learning in Early Childhood.